DIALECTICAL ISSUES ON CHARACTER EDUCATION IN KITAB ADAB AL-’ALIM WA AL- MUTA’ALLIM AS A FORM OF SOCIAL PIETY - Nafis, Muhammad Muntahibun (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2019)
This paper discusses the character education in Kitab Adab al-‘Alimwa al-Muta’allim, written by one of the founders of largest Muslim organization in Indonesia, Nahdlatul Ulama (1926), Kyai Hasyim Asy’ari as a form of social piety. This book has provided a comprehensive and constructive way of character education which integrates Islamic values with various religious texts. Character education which includes and complements a broad range of educational approaches such as social-emotional learning and civic education shares a commitment to help people become responsible and contributive citizens. Meanwhile, pesantren have taught and built strong characters of the santri in the forms of rabbaniyah (godness), insaniyah (humanity), wasathiyyah (moderateness) and waqi’iyyah (reality) characters. Therefore, pesantren-based character education the book described is a key element to nurture Muslims’ good habits. This paper shows that the book can be an answer for Indonesia’s contemporary multi-dimensional crises, such as radicalism and terrorism.